VITAL ARCHIVE GUARDIANS OF THE HILL AND WATER - Gamboa, Marianela (Instituto Regional de Planeamiento y Hábitat (RPHA), Unidad Doble dependencia CONICET y UNSJ, 2023)
This contribution is part of an ongoing artivist work that, at first, took the form of a photobook-fanzine and that I am currently re-editing for dissemination and invitation. Thus, in the process of rehearsing an affective ethno-photography to feed the memorial plot of the anti-extractivist feminist struggles of the collective spaces that I inhabit and the territories that I transit, I was composing from the image some fragments of the multi-situated vital archive of experiences. of defense, care and reproduction of life-in-common.